2018
DOI: 10.1002/jia2.25178
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent pregnancy at antiretroviral therapy (ART) initiation: a critical barrier to retention on ART

Abstract: IntroductionAdolescence and pregnancy are potential risk factors for loss to follow‐up (LTFU) while on antiretroviral therapy (ART). We compared adolescent and adult LTFU after ART initiation to quantify the impact of age, pregnancy, and site‐level factors on LTFU.MethodsWe used routine clinical data for patients initiating ART as young adolescents (YA; 10 to 14 years), older adolescents (OA; 15 to 19 years) and adults (≥20 years) from 2000 to 2014 at 52 health facilities affiliated with the International epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 28 publications
(35 reference statements)
3
26
1
Order By: Relevance
“…These findings correspond to those of Nuwagaba-Biribonwoha et al who found a greater rate of LTFU amongst pregnant and non-pregnant female adolescents, compared with male adolescents. 29 The current study reports lower RiC rates, compared with the 76.4% RiC at 12 months noted in a recent systematic review of pregnant and post-partum women in Africa. 30 This report found younger age and same-day ART initiation to be risk factors for poor retention, as was initiating during pregnancy, particularly late pregnancy.…”
Section: Proporɵon (%)contrasting
confidence: 54%
“…These findings correspond to those of Nuwagaba-Biribonwoha et al who found a greater rate of LTFU amongst pregnant and non-pregnant female adolescents, compared with male adolescents. 29 The current study reports lower RiC rates, compared with the 76.4% RiC at 12 months noted in a recent systematic review of pregnant and post-partum women in Africa. 30 This report found younger age and same-day ART initiation to be risk factors for poor retention, as was initiating during pregnancy, particularly late pregnancy.…”
Section: Proporɵon (%)contrasting
confidence: 54%
“…Many cohort studies have identified PL females as a particularly vulnerable group for attrition from HIV care [ 30 , 31 ]. Unfortunately, these studies also suggest that LTFU in this group has worsened despite increased numbers of pregnant women initiating ART under the Option B+ policy, which promotes lifelong ART for PL females regardless of CD4 count [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Included research suggests that amongst pregnant and parenting adolescents, additional challenges may emerge relating to HIV infection. Many adolescent mothers find out about their HIV status at the same time as their pregnancies are confirmed, often after their first trimester (Nuwagaba-Biribonwoha et al, 2018;Ronen et al, 2016), which may also be linked to delayed ART initiation for PMTCT. Two studies report that adolescent mothers living with HIV have less antenatal and postnatal care engagement, and are less likely to access programming that has shown to be effective among older mothers (Orne-Gliemann et al, 2017;Ronen et al, 2016).…”
Section: Adolescent Mothers Living With Hiv and Their Childrena Syndementioning
confidence: 99%